Improving Fiqh Learning Outcomes Through Problem Based Learning (PBL), Jigsaw, And Conventional Models Based On Interpersonal Intelligence Factors - Roby Salim; Wati Susilawati; Adam Malik (al-Afkar, Journal For Islamic Studies, 2025)
This research is shaped aside from seeing a dissatisfaction with the learning of the subjects of the students in the classroom. The objective of this study is to find out: 1) Differences in learning outcomes of students based on learning models (Problem Based Learning (PBL), Jigsaw and Conventional); 2) Difference in learners based on interpersonal intelligence (very good, good and good enough); 3) Interactions between learning models and interpersonnel intelligence in determining the learning outcome of students. The approach used in research is a quantitative approach to comparative methods. The results of the study showed that: 1) there was a difference in the learning outcome of the student based on the learning model (Problem Based Learning (PBL), Jigsaw and Conventional); 2) there was no difference in learning outcomes of students based on interpersonal intelligence (very good, good and fairly good), it was also found that the student with interpersonal intelligence is very different from the student who has good and sufficiently good interpersonnel intelligence; 3) There was no interaction between learning model and interpersons intelligence in determining the student's learning output.